Effect of Communication, Work Environment and Organizational Culture on Employee Performance at PT Lautan Belawan Jaya - Yeni Ariesa; Leni (Kusuma Negara Business School, 2021)
A system can run and operate properly and well if there is a regulation that really involves human resources. At PT Lautan Belawan Jaya this decline in employee performance can be seen from the failure to achieve sales targets and sales realization. Communication is one of the problems that occur in the company. Communication that involves employees with superiors, or fellow employees. In a company communication must be smooth but in this company the communication is not smooth because it is not verbal and there are several other factors. So that communication hinders the performance of employees. The work environment is also a problem in this company because there are many problems that employees feel uncomfortable at work such as noise and others. If the work environment is not comfortable, employees will also feel disturbed or uncomfortable so that performance is less. The organizational culture in this company is also slowly disappearing. Employees in this company do not follow the culture that has existed for a long time and are not role models in carrying out their daily work. Organizational culture that is not good so that employee performance is not good or decreases The purpose of this research is to know the influence of communication, work environment and organizational culture at PT Lautan Belawan Jaya. This research was conducted using primary data by distributing questionnaires to the company PT Lautan Belawan Jaya.